2021
DOI: 10.1039/d1na00475a
|View full text |Cite
|
Sign up to set email alerts
|

Nano-evolution and protein-based enzymatic evolution predicts novel types of natural product nanozymes of traditional Chinese medicine: cases of herbzymes of Taishan-Huangjing (Rhizoma polygonati) and Goji (Lycium chinense)

Abstract: Nanozyme and natural product-derived herbzyme have been identified in different enzyme types simulating the natural protein-based enzyme function. How to explore and predict enzyme types of novel nanozyme when synthesized...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Moreover, P. ginseng significantly elevated the GP serum level. Several studies (Al-Dabbagh et al, 2018;Li et al, 2020;Nazarbek et al, 2021) confirmed this finding. As well, the MDA serum level showed a significant reduction after the administration of P. ginseng, coinciding with a previous report (Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 64%
“…Moreover, P. ginseng significantly elevated the GP serum level. Several studies (Al-Dabbagh et al, 2018;Li et al, 2020;Nazarbek et al, 2021) confirmed this finding. As well, the MDA serum level showed a significant reduction after the administration of P. ginseng, coinciding with a previous report (Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 64%
“…However, so far carbon-based nonozymatic activities are limited to oxidase, peroxidase, superoxide dismutase and catalase activities [50,51]. The antitumor effect developed by nanozymes with oxidizing characteristics can be attributed to the reactive oxygen species (ROS) [50]. Different elements, natural products or metal-doped carbon-based nanozymes are developed to be used as sensor, anti-cancer therapeutic reagents [52][53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…Carbon-based nanozyme materials have been well studied and applied to various practices regarding their antitumor and antimicrobial effects. However, so far carbon-based nonozymatic activities are limited to oxidase, peroxidase, superoxide dismutase and catalase activities [50,51]. The antitumor effect developed by nanozymes with oxidizing characteristics can be attributed to the reactive oxygen species (ROS) [50].…”
Section: Discussionmentioning
confidence: 99%
“…The size distribution, zeta potential, and PDI of the micelles were determined by dynamic light scattering (DLS) using a Zetasizer Nano ZS-90 (Malvern, United Kingdom). Data were recorded at 25°C with a scattering angle of 90° ( Nazarbek et al, 2021 ; Xie et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%